Autonomous smart robot surveillance system (ASRSS) - Guat, Si Jie (2018)
This thesis describes an autonomous smart robot surveillance system which acts as a home surveillance system. The surveillance robot can automatically move from a surveilling sport to another and record plus send a notification to the user if there is a moving object recorded. It will upload the video to Google Drive. It can avoid moving object if it is moving in the direction of the robot.